THE ROLE OF COMMUNICATIVE APPROACH IN DEVELOPING SPEAKING SKILLS OF EFL LEARNERS - Jovliyeva Nafosat Bahodir qizi (ILMIY YANGILIKLAR VA INTELLEKTUAL TADQIQOTLAR, 2025)
Annotation: This article investigates the effect of multimedia tools on English vocabulary acquisition among EFL learners. The study focuses on how digital technologies such as videos, animations, and interactive applications improve vocabulary learning, retention, and motivation. The results show that the integration of multimedia tools provides visual and auditory support, enhances memory, and makes the learning process more engaging and effective. The paper also discusses challenges in implementation and provides recommendations for teachers to maximize the benefits of multimedia-assisted learning.